MICROHARDNESS OF TOOTH ENAMEL WITH DIFFERENT LEVEL OF RESISTANCE - N.L. Chukhray; V.A. Vynar (Український стоматологічний альманах, 2018)
This study about the microhardness of tooth enamel is evaluated by nanoidentation. The data indicate that the average microhardness of the enamel of the permanent teeth in the region of the equator is 5,75±0,06 Gpa, modulus of elasticity - 97,72±0,74 GPa on average data. It was revealed difference in indices of enamel microhardness, depending on the level of its enamel. Microhardness cariesresistant enamel of the permanent teeth is 7,85±0,10 GPa, which is higher than the corresponding mean for microhardness of relatively resistant enamel 6,45±0,06 GPa and significantly higher than caries susceptible enamel (2,95±0,22 GPa ). The relationship between enamel resistances with microhardness of its superfacial layers is showed. The highest mean of elasticity was found in samples of teeth with enamel resistant to dental caries (119,77±1,30 GPa), which is on 10,54% and 44,67% higher compared with the value of the index in samples of tooth with conditionally resistant and caries susceptible enamel.